Repair Of Ultrasonic Machining Induced Surface/Subsurface Cracks By Laser Irradiation - Pay, Jun Liew; Jingsi, Wang (Elsevier Ltd, 2019)
In ultrasonic machining (USM),a mirror-like surface cannot be readily obtained on hard and brittle materials owing to easily generated microcracks.This drawback greatly limits the utilisation of USM as a finish machining technology.Therefore,minimizing the crack size or even eliminating the cracks is necessary to improve surface quality.In this study,fine abrasive particles are first applied to minimize the crack size during USM. Material removal efficiency and surface quality are then evaluated.However,crack formation during this process is unavoidable,and microcracks left on the machined surface cannot be completely removed by merely decreasing the particle size.In addition,minimizing the particle size is not beneficial to maintaining a desired machining rate. Therefore,a new method to repair the cracks by laser irradiation is proposed.The USM machined surfacesm of glass plates are irradiated by a carbon dioxide laser at a wavelength of 10.6 μm to repair the cracks because glass has a high absorption coefficient at this wavelength.The temperature field generated during this process is evaluated using the finite element method. Simulation and experimental results demonstrate that the scanning speed of the laser beam has a considerable effect on the temperature increase,thereby influencing the repair result accordingly.Finally,a smoothed surface without cracks is obtained under a scanning speed of 300 mm/min and 5 W power.The combination of micro-USM and laser irradiation exhibits great potential for fabricating various micro-shapes and structures on hard and brittle materials,such as glass with high efficiency, high form precision and high surface quality.